2016
DOI: 10.1111/jcpe.12488
|View full text |Cite
|
Sign up to set email alerts
|

Loss of molars in periodontally treated patients: results 10 years and more after active periodontal therapy

Abstract: Overall, periodontal therapy results in a good prognosis of molars. Degree III FI, progressive BL, endodontic treatment, residual PPD, age, female gender, smoking, and diabetes mellitus strongly influence the prognosis for molars after APT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
129
4
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(151 citation statements)
references
References 45 publications
10
129
4
3
Order By: Relevance
“…Most previous studies investigating the different effects of degree of FI on tooth loss had concluded that a gradient effect exists increasing from degree I to II and then to III (Dannewitz et al., ; Graetz et al., ; Johansson, Johansson, & Ravald, ; McGuire & Nunn, ; Salvi et al., ). A meta‐analysis of this association concluded that RR of tooth loss was approximately 1.67 for degree II versus I, 1.83 for III versus II and 3.13 for degree III versus I (Nibali et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies investigating the different effects of degree of FI on tooth loss had concluded that a gradient effect exists increasing from degree I to II and then to III (Dannewitz et al., ; Graetz et al., ; Johansson, Johansson, & Ravald, ; McGuire & Nunn, ; Salvi et al., ). A meta‐analysis of this association concluded that RR of tooth loss was approximately 1.67 for degree II versus I, 1.83 for III versus II and 3.13 for degree III versus I (Nibali et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of molar survival time depending on the extent of furcation involvement represents relevant additional information. The increase in the risk of furcation involvement II and III has been defined (Dannewitz et al., ; Graetz et al., ; Martinez‐Canut, ), and also associated with smoking (Graetz et al., ). This tool itself can corroborate this finding and extend the information to the impact of other PRFs.…”
Section: Discussionmentioning
confidence: 99%
“…Furcation defects are a frequent finding in periodontitis patients (Dannewitz et al. , ). Molars affected with furcation involvement respond less favourably to periodontal therapy than molars without furcation involvement or single‐rooted teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that different classes of furcation involvement are related to different levels of prognosis (McGuire & Nunn , Dannewitz et al. , , Salvi et al. , Graetz et al.…”
Section: Discussionmentioning
confidence: 99%